Pengaruh Jarak Tanam dan Jenis Pupuk Kandang Terhadap Pertumbuhan dan Produksi Kacang Hijau (Vigna radiata L.) - Nining Haerani; Nurjannah -; Sofyan - (Jurnal Agrotan, 2023)
The growth and production of green bean plants can be increased by improving the right cultivation techniques, namely the treatment of spacing and improving soil fertility by applying manure. This study aims to determine the spacing and type of manure as well as their interactions with the growth and production of green bean plants. This research was conducted in Kassi-Kassi Hamlet, Toddopulia Village, Tanralili District, Maros Regency. The time used in this study started from May to August 2022. This study used a factorial design method with a basic randomized block design , with 9 treatment combinations and repeated 3 times so that there were 27 units with the first factor, namely the application of distance plant 20x20, 20x30, 20x40 cm and the second factor is the application of chicken manure, cow manure and goat manure. The results showed that the spacing of 20x40 cm had a significant effect on plant height (102.89 cm) and flowering time (128.33 dap). While the application of chicken manure had a significant effect on the growth of the number of leaves (63.33 strands).